Canadian Society for Exercise Physiology position paper: resistance training in children and adolescents - Behm, D. G.; Faigenbaum, A. D.; Falk, B.; Klentrou, P. (Applied Physiology, Nutrition, and Metabolism, 2008)
Many position stands and review papers have refuted the myths associated with resistance training (RT) in children and adolescents. With proper training methods, RT for children and adolescents can be relatively safe and improve overall health. The objective of this position paper and review is to highlight research and provide recommendations in aspects of RT that have not been extensively reported in the pediatric literature. In addition to the well-documented increases in muscular strength and endurance, RT has been used to improve function in pediatric patients with cystic fibrosis and cerebral palsy, as well as pediatric burn victims. Increases in children`s muscular strength have been attributed primarily to neurological adaptations due to the disproportionately higher increase in muscle strength than in muscle size. Although most studies using anthropometric measures have not shown significant muscle hypertrophy in children, more sensitive measures such as magnetic resonance imaging and ultrasound have suggested hypertrophy may occur. There is no minimum age for RT for children. However, the training and instruction must be appropriate for children and adolescents, involving a proper warm-up, cool-down, and appropriate choice of exercises. It is recommended that low- to moderate-intensity resistance exercise should be done 2-3 times/week on non-consecutive days, with 1-2 sets initially, progressing to 4 sets of 8-15 repetitions for 8-12 exercises. These exercises can include more advanced movements such as Olympic-style lifting, plyometrics, and balance training, which can enhance strength, power, co-ordination, and balance. However, specific guidelines for these more advanced techniques need to be established for youth. In conclusion, an RT program that is within a child`s or adolescent`s capacity and involves gradual progression under qualified instruction and supervision with appropriately sized equipment can involve more advanced or intense RT exercises, which can lead to functional (i.e., muscular strength, endurance, power, balance, and co-ordination) and health benefits.